Answer:
Point N
Step-by-step explanation:
Y² + 2 y - 2x - 3 = 0
x + 3 = y² + 2 y
2 x + 3 = y² + 2 x + 1 - 1
2 x + 3 = ( y + 1 )² - 1
2 x + 3 + 1 = ( y + 1 )²
Answer:
2 ( x + 2 ) = ( y + 1 )²
Answer : $22.50
Explanation: .30•25=7.5 30-7.5=22.5
Step 2 9y - 24 = 10 + 3y because 3 times 3y its not 6y nor is 3 times 8 equal to 5
Answer:
it has one solution
Step-by-step explanation:
1.y=x-3
2. 3y-3x sub x-3 in place of y therefore
it can also be written as 3x-3x-9=9
if you add 9 to both sides 3x-3x-9+9=-9+9
0+0=0